Gasgeochemical features in the western part of the East Vietnam Sea (Bien Dong Sea) - N. S., Syrbu; Nguyen, Hoang; R. B., Shakirov; A. O., Kholmogorov; A. L., Venikova; Le, Duc Anh; A. A., Legkodimov (Vietnam Journal of Marine Science and Technology, 2022)
During the joint Russian-Vietnamese studies in the East Vietnam Sea (known as Bien Dong or the South China Sea), manifestations of new hydrocarbon-accumulating zones were discovered; evidences of the presence of mineral indicators for solid minerals in shelf deposits were obtained; a unique zone, where accumulations of ferromanganese crusts and nodules have been formed, was revealed for the first time; evidence of unique properties of deep-water fine-dispersed carbonate sediments (which makes it possible to attribute them to an independent type of mineral resources of the East Vietnam Sea) were obtained; the ikaite mineral (that serves as an indicator of methane migration zones and cold marine paleo-conditions) was discovered in the Phu Khanh basin; heavy concentrates with indicators of rare forms of ore mineralization were collected; features of methane and mercury fluxes into the atmosphere, cultures of methane-oxidizing, oil-oxidizing and sulfate-reducing bacteria were registered for the first time within the study areas. New data on gravity and magnetic field anomalies along the shelf and slope of Vietnam have been obtained. The article presents the results of coastal geophysical and gasgeochemical research obtained in 2010–2020 within the Joint Russian-Vietnamese Laboratory for Marine Geosciences (POI FEB RAS - IMGG VAST). For the first time, anomalous methane fields (comparable to anomalies on the oil- and gas-bearing shelf and the gas hydrate-bearing slope of Sakhalin Island) were registered in the water column. The gravimagnetic survey was carried out on the central and southern shelf and the continental slope of Vietnam; the executed works supplemented the geophysical data, which had been obtained in the 80s–90s of the preceding century. The paper contributes to the Russia-Vietnamese program within the UN Decade of Ocean Sciences for Sustainable Development framework.